2014
DOI: 10.5267/j.msl.2013.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance and intellectual capital

Abstract: The purpose of this paper is to examine the association between corporate governance and Intellectual capital in the pharmaceutical companies accepted in Tehran Stock Exchange over the period 2004-2009 using a regression based model. The study investigates the impacts of three some independent variables of the corporate governance (i.e. the number of board members, the relative extent of nonexecutive to executive directors, the auditing committee). The results suggest that corporate governance had no special e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 11 publications
4
10
0
Order By: Relevance
“…Similarly, NEXD has a positive and significant relationship with HCE, SCE and RCE value of the IBs. These results are consistent with (Alizadeh et al, 2014;Kamath, 2019), where they found that NEXD prefers to enhance the value of ICE. Thus, the results are consistent with the stakeholder theory, which explains that board with the majority of NEXDs is in favour to lessen the top management exploitation of shareholders' wealth, and efficient use of IC added the value for the IBs.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Similarly, NEXD has a positive and significant relationship with HCE, SCE and RCE value of the IBs. These results are consistent with (Alizadeh et al, 2014;Kamath, 2019), where they found that NEXD prefers to enhance the value of ICE. Thus, the results are consistent with the stakeholder theory, which explains that board with the majority of NEXDs is in favour to lessen the top management exploitation of shareholders' wealth, and efficient use of IC added the value for the IBs.…”
Section: Resultssupporting
confidence: 90%
“…The function of the AUDC in monitoring the reporting process has been widely discussed in the literature (Chou and Buchdadi, 2017;Mahmudi and Nurhayati, 2015). While some studies found positive and significant relationship (Li et al, 2012;Mahmudi and Nurhayati, 2015), some studies found negative (Alizadeh et al, 2014) and few studies found insignificant relationship (Appuhami and Bhuyan, 2015) of AUDC with ICE. Thus, the current study proposes the following hypothesis to explore this complicated relationship in IBs.…”
Section: Audit Committee (Audc)mentioning
confidence: 99%
“…Corporate governance plays an essential role in making important investment decisions. Various studies regarding the impact of corporate governance on different categories such as IC (Alizadeh et al , 2014) have been conducted over the years. Corporate governance encompasses how organizational structures are managed by companies on the aspects of culture, policies, strategies and ways of dealing with different stakeholders (Barrett, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…There have been a number of methodological frameworks developed as well as empirical examinations on IC. A number of studies have examined the effect of IC on firm performance (Firer & Williams, 2003;Goh, 2005;Kamath, 2007;Riahi-Belkaoui, 2003), corporate governance (Abeysekera, 2010;Al-Musalli & Ismail, 2012;Alizadeh, Chashmi, & Bahnamiri, 2014;Keenan & Aggestam, 2001;Li, Pike, & Haniffa, 2008;Makki & Lodhi, 2014), corporate social responsibility (Aras, Aybars, & Kutlu, 2011;Musibah & Alfa, 2013) and market value (Chen, Cheng, & Hwang, 2005;Maditinos, Chatzoudes, Tsairidis, & Theriou, 2011;Nimtrakoon, 2015;Sharma, 2018) among others. In spite of the increasing research into these relationships, there is little evidence on the determinants of IC.…”
Section: Introductionmentioning
confidence: 99%